The Role of IL-5, IL-33 and Total IgE in a Sample of Workers Suffering from Paints and Mills Asthmatic Patients - Ruaa Adnan Ali (Institute of Medico-legal Publications Pvt Ltd, 2022)
A case-control retrospective study was conducted during November 2020 on 88 asthmatic patients (38 male mill and 50 male paints workers)with age ranged between (15-25),and 44 control with age ranged between (15-25)years to assess the role of total IgE ,interleukine5(IL-5),and interleukin33(IL-33)serum levels in pathophysiology of disease using ELISA and multiplex immunoblot kits. Some hematological changes such as(Eosinophil and Basophil%)by Beckman coulter. The patients’ samples were obtained from Nature Dyes Company Ltd in the industrial region of Aweerij Industrial, as well as Al-Dora flour mill in Baghdad, which is part of the general company for grain processing. The tests were carried out at the Specialized Center of Allergy in Baghdad/Al-Rusafa from October 2020 to April 2021. Specialized respiratory disorders and Asthma diagnose these cases, which are clinically diagnosed according to international guide lines. The present study confirms the highly significant role of total IgE and IL5,IL-33 levels compared with control in pathophysiology of bronchial asthma and it correlation with disease severity and allergen type in adults. Results showed that there were highly significant increase in Eosinophil and basophil % in cases asthma of paints and mills patients with control group. In addition, there were a positive correlation between Eosinophil and Basophil in asthma of paints, and in asthma of mills. There was positive correlation between total IgE with IL-5 and IL-33 in asthmatic group.